A Comprehensive Systematic Review of Management of Normal Tension Glaucoma - Michelthelia Sulijaya Suyono; Benso Sulijaya Suyono (International Medical Journal Corp. Ltd, 2026)
Introduction: Normal tension glaucoma (NTG) represents a significant diagnostic and therapeutic challenge within the spectrum of open-angle glaucomas. Characterized by progressive optic neuropathy and visual field loss despite intraocular pressure (IOP) measurements consistently within the statistically normal range, its management remains complex and debated. The central question persists: is IOP reduction beneficial in NTG, and if so, what is the optimal therapeutic strategy? (Anderson et al., 2003). Methods: This comprehensive systematic review was conducted in strict accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. A thorough literature search and screening process identified 80 eligible studies, including randomized controlled trials, cohort studies, and meta-analyses. Inclusion criteria focused on studies evaluating therapeutic interventions (medical, laser, surgical) for NTG with a minimum follow-up of 6 months. Data extraction encompassed management approaches, clinical outcomes (IOP, visual fields, optic disc), patient characteristics, and adverse effects. Results: The synthesis of evidence reveals that IOP reduction, even from normal baseline levels, is beneficial in slowing NTG progression. Medical therapy, particularly prostaglandin analogues (PGAs) like latanoprost, provides an average IOP reduction of 16-24% (Cheng et al., 2009; Ang et al., 2004). Selective laser trabeculoplasty (SLT) achieves comparable efficacy, with first-line use showing superior outcomes (Nitta et al., 2024; Naito et al., 2025). Surgical interventions, including trabeculectomy and minimally invasive glaucoma surgery (MIGS), offer greater and more sustained IOP lowering (30-40%) and reduce medication burden (Chin Lai et al., 2022; Hnin P Oo et al., 2024). Critically, a ≥25% IOP reduction from baseline is associated with significant suppression of visual field progression (Yoshikawa et al., 2018). Evidence also supports pressure-independent neuroprotective effects, notably with brimonidine (Sena & Lindsley, 2017; Krupin et al., 2005) and nilvadipine (Koseki et al., 2008). Discussion: The findings advocate for a stratified, patient-centric management paradigm. Treatment efficacy is strongly influenced by baseline IOP; patients with higher baseline IOP (>15 mmHg) respond better to conventional IOP-lowering therapies. In contrast, patients with lower baseline IOP require consideration of adjunctive neuroprotective strategies and management of vascular risk factors like disc hemorrhage and nocturnal blood pressure dipping (Lee et al., 2014; Bowe et al., 2015). Long-term safety considerations, such as prostaglandin-induced central corneal thinning (Kim & Cho, 2011; Hyungwoo Lee & Cho, 2015) and surgical complication profiles (Andrea Gabai et al., 2019), must be balanced against therapeutic benefits. Conclusion: Effective management of NTG necessitates a multifaceted approach centered on achieving substantial IOP reduction, with a target of ≥25% being clinically meaningful. Treatment selection should be individualized based on baseline IOP, risk factor profile, disease severity, and patient tolerance. Future research should prioritize long-term outcomes of novel interventions, refined patient stratification biomarkers, and the integration of neuroprotection into standard care protocols.